2019
DOI: 10.1371/journal.pone.0217373
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between leukocyte aldo-keto reductase 1C3 activity, genotypes, biological, lifestyle and clinical features in a prostate cancer cohort from New Zealand

Abstract: Introduction Aldo-keto reductase 1C3 (AKR1C3) is known for multiple functions including its catalytic activity towards producing extra-testicular androgen. The present study is towards understanding interaction between biological, lifestyle and genetic impacts of AKR1C3 and their influence on clinical factors in a prostate cancer (PC) cohort from New Zealand (NZ). Method Characteristics of 516 PC patients were collected from the Auckland Regional Urology Facility, NZ. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…AKR1C3 is known as an epithelial-mesenchymal transition driver in prostate cancer metastasis [46] . In a small group of men with prostate cancer from NZ, we have shown a signi cant increase in leukocyte AKR1C3 activity level with age at diagnosis, and upon genetic strati cation this shows a trend among cases carrying the AKR1C3 rs12529 GG genotype only [24] . Additionally, our previous study showed that men carrying the AKR1C3 rs12529 GG genotype carry higher levels of leukocyte AKR1C3 activity, if their PSA was > 20ng/ml, compared to those carrying a PSA level ≤ 20ng/ml.…”
Section: Ea Controls Cohort From the Physicians'mentioning
confidence: 75%
See 3 more Smart Citations
“…AKR1C3 is known as an epithelial-mesenchymal transition driver in prostate cancer metastasis [46] . In a small group of men with prostate cancer from NZ, we have shown a signi cant increase in leukocyte AKR1C3 activity level with age at diagnosis, and upon genetic strati cation this shows a trend among cases carrying the AKR1C3 rs12529 GG genotype only [24] . Additionally, our previous study showed that men carrying the AKR1C3 rs12529 GG genotype carry higher levels of leukocyte AKR1C3 activity, if their PSA was > 20ng/ml, compared to those carrying a PSA level ≤ 20ng/ml.…”
Section: Ea Controls Cohort From the Physicians'mentioning
confidence: 75%
“…Other AKR1C3 genetic polymorphisms have also been associated with benign prostate hyperplasia-related factors including dihydrotestosterone inactivation and prostate volume [23] . Meanwhile, our data suggests that the age-based PSA variation is restricted to the AKR1C3 rs12529 CG and GG genotype carriers in a New Zealand (NZ) prostate cancer cohort [24] . In that study, we also showed that ever-smoking in uenced both age and PSA at prostate cancer diagnosis among the AKR1C3 rs12529 GG and CG genotype carriers, respectively.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…There was no overall significant correlation between the difference in serum selenium after supplementation and subsequent difference in PSA level, although significant correlations were recorded among, men below the median age of 55 years as well as the group who were never-smokers. Our previous studies have shown that age based PSA increase in men with prostate cancer beyond 69 years could be due to the increase in extra-testicular androgen production from adrenal dehydroepiandrosterone (DHEA)-based androgen precursors [65] catalyzed by the AKR1C3 enzyme, particularly among men carrying the AKR1C3 rs12529 CG and GG genotypes [66]. Therefore, our current observation of a significant inverse correlation between the difference in serum selenium and difference in PSA level after selenium supplementation among men below the age of 55 years may indicate that increased selenium level does not support a significant reduction in PSA when the extra-testicular androgen production starts to increase with advancing age.…”
Section: Discussionmentioning
confidence: 99%